Effects of diversity schemes and correlated channels on OWC systems performance. Issue 21 (30th November 2017) - Alimi, Isiaka A.; Shahpari, Ali; Monteiro, Paulo P.; Teixeira, António L.
Abstract: The salient features and advantages of free-space optical (FSO) system are very appealing for different applications in a number of communication network sectors. In spite of the advantages and diverse applications of FSO communication, its extensive use is hindered by the atmospheric turbulence-induced fading in real-life scenarios. Spatial diversity technique is one of effective means of mitigating turbulence-induced fading and, consequently, improves the system performance. In this paper, we study the spatial diversity schemes for mitigating turbulence-induced fading in the FSO communication systems using the bit error rate (BER) as a performance metric. The schemes considered are based on orthogonal space–time block codes and repetition codes (RCs). We derive simple approximate closed-form expressions for the error probability of the log-normal FSO links with intensity modulation and direct detection (IM/DD). Furthermore, we also investigate the effects of spatial correlation between the transmit apertures on the system performance. We achieve this using the exponential model for determining the correlations between the apertures. We observe that the proposed BER expressions are able to quantify the effects of spatial diversity schemes and spatial correlations on the system.